Real-time quantitative PCR assay with Taqman® probe for rapid detection of MCR-1 plasmid-mediated colistin resistance. (September 2016) - Chabou, S.; Leangapichart, T.; Okdah, L.; Le Page, S.; Hadjadj, L.; Rolain, J.-M.
Abstract: Here we report the development of two rapid real-time quantitative PCR assays with TaqMan ® probes to detect the MCR-1 plasmid-mediated colistin resistance gene from bacterial isolates and faecal samples from chickens. Specificity and sensitivity of the assay were 100% on bacterial isolates including 18 colistin-resistant isolates carrying the mcr-1 gene (six Klebsiella pneumoniae and 12 Escherichia coli ) with a calibration curve that was linear from 10 1 to 10 8 DNA copies. Five out of 833 faecal samples from chickens from Algeria were positive, from which three E. coli strains were isolated and confirmed to harbour the mcr-1 gene by standard PCR and sequencing.